Reverse Logistics for Return Management in Retail: A Systematic Literature Review from 2007 to 2016 - Dias, K. T. S. [UNESP]; Braga, S. S. [UNESP]; Silva, D. [UNESP]; Satolo, E. G. [UNESP]; Mula, J.; Barbastefano, R.; DiazMadronero, M.; Poler, R. (Springer, 2019)
Business logistics, both integrated and reverse, is an important activity in the supply chain, capable of managing raw materials, stocks, transport and information. With regard to reverse logistics, it is developed in the processes of return management, which plays a critical role in the management of organizations. The retail sector, besides being one of the main recipients of returned products and packaging, plays a fundamental role in the supply chain and has a significant participation in issues of dissemination of social and environmental responsibilities. Thus, given the representativeness of retail and the importance of the reverse logistics activity, this study aimed to analyse the publications of articles, between 2007 and 2016, regarding the use of reverse logistics for the management of returns in retail. Through a systematic literature review, the results show that the studied subject is still in development, since, from the 116 references found, only 10 were considered for the final analysis of this present study. Another factor that reaffirms this evidence is the predominant exploratory character of all the available research, and the fact that half of the studies selected for the final analysis were published in the last year (2016). Furthermore, it was possible identify that advantages obtained by reverse logistics management is, principally, related in economic and environmental scope.
Keywords: Reverse logistics; Retail; Return management; Systematic literature review